Acoustic detections of beaked whales, narrow-band high-frequency pulses and other odontocete cetaceans in the Southern Ocean using an autonomous towed hydrophone recorder. (November 2021) - Barlow, Jay; Cheeseman, Ted; Trickey, Jennifer S.
Abstract: Encased in a streamlined, flooded housing, a SoundTrap ST300HF hydrophone recording system was towed on voyages to South Georgia Island and the South Sandwich Islands and to the Antarctic Peninsula in December 2019–February 2020. Recordings were analyzed to identify acoustic detections of cetacean species. Acoustically identified species included sperm whales ( Physeter macrocephalus ), southern bottlenose whales ( Hyperoodon planifrons ), Arnoux's beaked whales ( Berardius arnuxii ), killer whales ( Orcinus orca ), and long-finned pilot whales ( Globicephala melas ). Acoustic detections also included several recognized types of beaked whale echolocation pulses (BW37/39 and BW58) as well as two likely beaked whale echolocation pulse types that do not match any previous descriptions. Narrow-band high-frequency echolocation signals (NBHF) (typical of porpoises and some dolphin species) were detected in many locations, and one of these coincided with a sighting of hourglass dolphins ( Lagenorhynchus cruciger ). This study shows the utility of an autonomous towed hydrophone system on a vessel of opportunity to study the distribution of cetaceans in rough seas that are difficult to study by visual survey methods.